PENGARUH PELATIHAN, PENGALAMAN KERJA DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP PRESTASI KERJA PEGAWAI DI POLITEKNIK PENERBANGAN MEDAN - Inda Tri Pasa (JRMB (Jurnal Riset Manajemen & Bisnis), 2021)
Employee job achievement is one of the important factors to know the overall performance of the institution is doing well, to improve employee job achievement is influenced by various factors. This research aims to find the effect of training, work experience and human resources competency on job achievement. Various obstacles factors to improve employee job achievement should be able to known by institution as a whole in improving employees job achievement. This method of study used samples of 73 civil servants at Medan Aviation Polytechnic. The data used is the data of the employees and institutions in the year 2020. For data processing, the author uses SPSS software version 26. As for the results of this study, demonstrated Training and Human Resources Competency has significant positive impact on Job Achievement, while Work Experience has no effect on Employee Job Achievement at Medan Aviation Polytechnic. Based on multiple linear regression test results, t test (partial) based on significance value 0.05, Training (X1) Sig value 0.031 0.05; Work Experience (X2) Sig 0550 0.05; and Human Resource Competency of Sig value 0.000 0.05. Based on t count value and t table value, Training (X1) of t count value 2,200 1,994; Work Experience (X2) value t count 0601 1,994 and Human Resource Competency of t count value 6,053 1,994. The test result F (simultaneous) based on the value of Sig 0.05, the calculation result of the independent variable (X) of the sig 0.000 value 0.05 states the independent variable (X) has a simultaneous effect on the dependent variable (Y). F (simultaneous) test results are based on the f count and t table values, the independent variable (X) is simultaneously affected by the dependent variable (Y) with the value F 38.485 2.74. Based on great influence (%) independent variable (X) to the dependent variable (Y) large impact of the Independent (X) variable is 62.6%. And the rest is influenced by other variables that are not researched by the author. To improve job achievement of employees, Medan Aviation Polytechnic, need to increase the number of training and improve existing human resource competency, because these two variables have an influence on the job achievement of employees at Medan Aviation Polytechnic.